2020
DOI: 10.1155/2020/3582947
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Selected Berries, Grapes, and Citrus Fruit as Neuroprotective Agents

Abstract: A healthy diet should nourish the brain with essential nutrients, including bioactive compounds, for normal brain functioning and to protect it from the negative effects of inflammation and oxidative stress. In this review, a concise summation of the protective effects of selected fruits, namely, berries, grapes, and citrus fruits, against neurological disorder is presented. The focus is on the neuroprotective potential of these fruits against neurodegenerative and mental disorders. The fruits selection was ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…Likewise, only low to moderate antioxidant properties have been reported for C. reticulata and C. limon peel essential oils [ 61 , 72 ]. Nevertheless, irrespective of their relatively weak antioxidant activity, the multitude of phytochemicals from citrus fruits may contribute to their purported neuroprotective properties [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, only low to moderate antioxidant properties have been reported for C. reticulata and C. limon peel essential oils [ 61 , 72 ]. Nevertheless, irrespective of their relatively weak antioxidant activity, the multitude of phytochemicals from citrus fruits may contribute to their purported neuroprotective properties [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that polyphenols in berries could remodel the amyloid‐beta accumulations, which is the primary process of cerebral damage in Alzheimer's disease. Also, blueberry could alleviate the inflammation of microglial cells through inflammatory mediator reduction 3,96,97 …”
Section: Antioxidant Activity In Herbs and Fruits And Its Effects On ...mentioning
confidence: 99%
“…Given the adverse effect of alcohol on the neurobehavior and embryonic development of the zebrafish larvae, Liu et al evaluated the protective effects of these glycoside flavanones (naringin, hesperidin, and naringenin) on the developmental defects and thigmotaxis induced by alcohol in those larvae. Using behavioral tests, they found that acute exposure to 1% alcohol‐induced thigmotaxis in zebrafish larvae 3 and 5 days after fertilization; however, these antioxidants could inhibit this behavior and reduce the alcohol‐induced morphological defects and apoptosis if they are administered during its development 3,96 . Furthermore, a diet containing orange juice could improve the cognitive function of healthy elderly in 8 weeks because it was rich in flavanone 104,105 …”
Section: Antioxidant Activity In Herbs and Fruits And Its Effects On ...mentioning
confidence: 99%
See 2 more Smart Citations